2002
DOI: 10.1079/joh2002134
|View full text |Cite
|
Sign up to set email alerts
|

Helminth communities of two sympatric skinks (Mabuya agilis and Mabuya macrorhyncha ) from two ‘restinga’ habitats in southeastern Brazil

Abstract: The helminth fauna of two sympatric congeneric skinks (Mabuya agilis and M. macrorhyncha) from two distinct "restinga" habitats (Praia das Neves and Grussaí) in southeastern Brazil were studied, totalling four data sets (sample sizes ranging from 11 to 28). A total of ten helminth species were associated with the skinks: Raillietiella sp., Paradistomum parvissimum, Pulchrosomoides elegans, Oochoristica ameivae, Hexametra boddaertii, Parapharyngodon sceleratus, Physalopteroides venancioi, Physaloptera sp., an u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
42
2
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(49 citation statements)
references
References 27 publications
4
42
2
1
Order By: Relevance
“…In Brazil, the studies have shown unequal prevalence in native lizards species Mabuya agilis (3.6-9.0%; Vrcibradic et al, 2002); Cnemidophorus abaetensis (6.0%; Dias et al, 2005), and C. ocellifer (2.5%; Dias et al, 2005); and Tropidurus hispidus (11.1%; Almeida et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Brazil, the studies have shown unequal prevalence in native lizards species Mabuya agilis (3.6-9.0%; Vrcibradic et al, 2002); Cnemidophorus abaetensis (6.0%; Dias et al, 2005), and C. ocellifer (2.5%; Dias et al, 2005); and Tropidurus hispidus (11.1%; Almeida et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…In Brazil, few works concerning raillietiellids as lizard parasites have been reported: Raillietiella freitasi in the lungs of Thrachylepis atlanticus (formerly Mabuya punctata), from Fernando de Noronha Island (situated on the northeastern coast) (Motta, 1963;Motta and Gomes, 1968;Rego, 1983;1984); larvae of Raillietiella sp. in skink Mabuya agilis reported by Vrcibradic et al (2002); Dias et al (2005) …”
Section: Introductionmentioning
confidence: 96%
“…Rallietiellids infecting lizards in Brazilian continental ecosystems were firstly recorded by Vrcibradic et al (2002) and Dias et al (2005). Vrcibradic et al (2002) reported only larvae of Raillietiella sp.…”
Section: Introductionmentioning
confidence: 97%
“…About 40 species of raillietiellids have been described in the world, but the Neotropical diversity of pentastomids has not received much academic attention and remains poorly known (Almeida and Christoffersen, 1999;2002). An attempt to survey the genus Raillietiella in Brazil generated only three recorded species: R. freitasi (Motta and Gomes, 1968), R. furcocerca (Diesing, 1863) and R. gigliolii Hett, 1924.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation